Post-fire cross-sectional behaviour of hot-rolled austenitic stainless steel channel section stub columns under combined compression and minor-axis bending - Li, Shuai (2023)
The present paper reports experimental and numerical investigations into the post-fire cross-sectional behaviour and residual resistances of hot-rolled austenitic stainless steel channel section stub columns under combined compression and minor-axis bending. An experimental programme included heating, soaking and cooling of specimens as well as post-fire initial local geometric imperfection measurements and minor-axis eccentric compression tests on fourteen specimens. The minor-axis eccentric compression test results were used in a parallel numerical modelling programme for validation of finite element models, which were then adopted to perform a series of parametric studies to generate further numerical data. Since there are no existing design rules for stainless steel structures after exposure to elevated temperatures, the relevant codified ambient temperature design interaction curves in combination with post-fire material properties were evaluated for their applicability to eccentrically loaded hot-rolled austenitic stainless steel channel section stub columns after exposure to elevated temperatures. The evaluation results revealed that the design interaction curves given in the European code and American specification led to rather conservative and scattered resistance predictions, which were attributed to the conservative end points and inefficient shapes. To address the shortcomings, new design interaction curves anchored to more accurate end points and having more efficient shapes were developed and resulted in more accurate and consistent resistance predictions than their codified counterparts. The reliability of the new design interaction curves was also confirmed by means of statistical analyses.